Pengaruh Latihan Ball Handling terhadap Peningkatan Keterampilan Dribbling Siswa dalam Pembelajaran Ekstrakurikuler - Wawan Muhammad Azlan; Muhammad Husni Tamim; Prietia Eko Wardoyo (Indonesian Journal of Islamic Educational Review, 2026)
Dribbling ability is one of the key fundamental technical skills in basketball as it underpins ball control and player movement during a match. Within the SMK Negeri 3 Selong basketball team, players’ dribbling abilities are not yet consistent, so more specific training is required to improve ball control. This study aims to analyse the effect of ball-handling training on dribbling skills in the SMK Negeri 3 Selong basketball team. The study employed a quantitative approach using an experimental method and a pre-experimental design in the form of a One-Group Pre-test-Post-test Design. The research subjects consisted of 15 students who were members of the SMK Negeri 3 Selong basketball extracurricular team. Dribbling ability was measured before and after the ball-handling training programme, and the data were analysed using a Paired Sample T-Test with the aid of SPSS version 25. The results showed an improvement in dribbling ability, with the mean score rising from 63.73 in the pre-test to 86.06 in the post-test. The results of the Paired-Sample t-test showed a significance value of 0.000 (0.05), indicating a difference in dribbling ability before and after the ball-handling training programme. These findings suggest that ball-handling training can serve as a relevant form of technical training to support the improvement of dribbling ability among school-level basketball players.